Motivating Multigenerational Employees: Is There a Difference? - Cote, Robert (Journal of Leadership, Accountability and Ethics, 2019)
Today, organizations are faced with a diverse multi-generational workforce that may require different strategies for motivating employees to be engaged in their job and increase job satisfaction. These challenges may be the result of several factors, including trust with management, lack of job recognition, opportunities based on skills, positive relationships, and lack of compensation for their efforts. By evaluating motivational theories, employee’s needs, and behaviors, organizations can develop and implement programs tailored specifically to increase motivation and drive performance. Motivational theories were developed in the 1940’s, 1950’s, and 1960’s and the concepts and principles were applicable to Baby Boomers and previous generations, i.e., Traditionalists or Silent Generation born prior to 1945. The premise of this paper is to further explore the application of motivational theories in all generations. This paper will provide a variety of strategies developed and implemented to motivate employees based on their individual differences. The strategies will take into consideration key factors, including intrinsic (internal) rewards, extrinsic (external) rewards, individual needs, behaviors, personal factors, and organizational factors. Can the findings conclude whether motivation needs are the same or different for the multigenerational workforce? Further research may be needed to explore the application of motivational theories and motivation programs with generation’s post 1960’s.